Pendidikan Kewarganegaraan di Era Digital (Perspektif Teori Sosialisasi Politik) - Muh. Hanif; Novala Arum Salsabillah (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2024)
The development of digital technology has brought fundamental changes in the way individuals obtain and process political information. This article discusses the dynamics of civic education in the digital era through the perspective of political socialization theory. This theory explains how individuals form political attitudes, values and behaviours through interactions with various socialization agents, such as family, schools, peers and mass media, which are now expanded by the presence of digital media. Civic education plays a strategic role in shaping young people's political awareness in the midst of massive, fast, but often unverified information flows. This research uses a qualitative approach with a literature study method, examining various academic literatures on political socialization and civic education in the digital era. This article highlights the importance of integrating digital literacy in the civic education curriculum to equip students with critical thinking skills, digital ethics, and the ability to participate actively and responsibly in political life. Thus, civic education in the digital era not only aims to produce information-literate citizens, but also to shape democratic, inclusive and reflective political characters.